Indonesian National Army: A Human Capital Strategy to Modernized National Army Power - Iman Permana; Muhammad Dhany Afrihan; Ignatius Candra Perwira (Budapest International Research and Critics University, 2022)
Human capital is a main core key success in the national defense, as well as in aspect of quantity but also in quality aspect. Indonesian National Army (TNI) needs to focus with a human capital strategy along with the development of sophisticated defense technology. TNI must leave the human resources strategy to create a professional modernize national army human capital. The human capital strategy focusing on necessary skills and the ability to operate, to produce, and to develop independently, as well makes the human resources into a human capital of TNI. TNI facing fourth-generation warfare today, which are: land warfare, navy warfare, air warfare, and cyber warfare? TNI need to build its defense force to protecting national resources. Indonesia's need a professional TNI as a human capital in a defense force to be supported by adequate defense appropriate weapons technology. Professionalism in the defense of human capital is also necessary that involve civilian defense in managing the future war like space warfare. The dynamics of international relations have been changed vis-à-vis with the defense technology. TNI need to prepare their human resources competency into a human capital. TNI competency is articulated in the norms of ideology, idealist, and innovative, creative, and high intelligent skills. In the current globalization, civilian and military roles are equally important to create human resources become human capital which can produce defense technology with deterrence effect. TNI can be seen as fundamental framework to create human capital strategy in protecting national interest.